New approaches to the pharmacotherapy of neuropathic pain. Issue 5 (September 2008) - Besson, Marie; Piguet, Valérie; Dayer, Pierre; Desmeules, Jules
Pain is one of the most debilitating symptoms that presents with neuropathy. Neuropathic pain syndrome is a challenge to treat and, even with appropriate evidence-based treatment, only a 40% reduction of symptoms can be achieved in approximately half of patients. Furthermore, efficient doses are often difficult to obtain because of adverse effects. These observations underline that the treatment of neuropathic pain is still an unmet medical need. New approaches to the pharmacotherapy of neuropathy embrace different lines of work, including a fundamental mechanism-based approach, a clinical mechanism-based approach and an evidence-based approach. Moreover, interindividual variability in drug response, and genetic polymorphism in particular, is an emerging aspect to consider. Together with reviewing recent evidence-based guidelines as well as briefly discussing genetic polymorphisms that may influence the individual responses to treatments, this article will focus on what a mechanism-based approach is bringing to the clinical setting, on the perspective in fundamental research and on the difficulty of bridging the gap between fundamental notions and positive clinical outcomes.